2014
DOI: 10.1111/nph.12799
|View full text |Cite
|
Sign up to set email alerts
|

The contrasting effects of genome size, chromosome number and ploidy level on plant invasiveness: a global analysis

Abstract: SummaryUnderstanding how species' traits relate to their status (e.g. invasiveness or rarity) is important because it can help to efficiently focus conservation and management effort and infer mechanisms affecting plant status. This is particularly important for invasiveness, in which proactive action is needed to restrict the establishment of potentially invasive plants.We tested the ability of genome size (DNA 1C-values) to explain invasiveness and compared it with cytogenetic traits (chromosome number and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
106
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(117 citation statements)
references
References 68 publications
8
106
3
Order By: Relevance
“…This is in accordance with surveys that had been conducted by Fernald (1903) and Mulligan (1958) in eastern North America where only a few populations of L. ircutianum were found. The higher invasion success of the diploid L. vulgare is in contrast to studies that found a positive association between polyploidy and invasiveness in plants (Lafuma et al 2003;Kubátová et al 2008;Schlaepfer et al 2008;Treier et al 2009;Pandit et al 2011Pandit et al , 2014te Beest et al 2012). The higher abundance of L. vulgare in the introduced range could potentially be explained by differences in introduction pressure between the two species.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…This is in accordance with surveys that had been conducted by Fernald (1903) and Mulligan (1958) in eastern North America where only a few populations of L. ircutianum were found. The higher invasion success of the diploid L. vulgare is in contrast to studies that found a positive association between polyploidy and invasiveness in plants (Lafuma et al 2003;Kubátová et al 2008;Schlaepfer et al 2008;Treier et al 2009;Pandit et al 2011Pandit et al , 2014te Beest et al 2012). The higher abundance of L. vulgare in the introduced range could potentially be explained by differences in introduction pressure between the two species.…”
Section: Discussioncontrasting
confidence: 53%
“…Polyploidy has been found to be overrepresented in invasive plants (Pandit et al 2011(Pandit et al , 2014 and in various taxa with more than one ploidy level in the native range, only polyploids have become invasive (e.g. Lafuma et al 2003;Kubátová et al 2008;Schlaepfer et al 2008;Treier et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-three of the 25 most-studied weedy plant species have 1C genome sizes of less than 5,000 Mb, and 13 of these have genome sizes of less than 2,000 Mb . Recently, a meta-analysis was performed in which invasiveness among plant species was negatively associated with genome size and positively associated with chromosome number (Pandit et al, 2014). This study analyzed 890 species among 62 genera.…”
Section: Discussionmentioning
confidence: 99%
“…Allopolyploidy, i.e. hybrid polyploidy, does not seem to correlate to larger ranges either [90], but intriguingly, two extensive studies in plants show it is more frequent in high latitudes [91] and in invasive plant species [92]. The abundance of polyploid morphs in northern biota, termed 'geographic polyploidy', was already an object of speculation by Vandel [1].…”
Section: (B) Models In Which Correlates Of Parthenogenesis Rather Thamentioning
confidence: 99%